Bezpośrednie inwestycje zagraniczne w Polsce - Kozuń-Cieślak, Grażyna (Foreign Direct Investment in Poland, 2006)
The fast globalization process of world economy has intensified the circulation of capital in the form of foreign direct investment (FDI). This form of investment is especially welcome by host countries since, besides a lot of money, it provides know how. That is why it can be said that FDI is an object of competition, especially among developing countries. On the other hand, activity on foreign markets is an indicator of increased efficiency of business that seeks the most advantageous forms of capital allocation. The goal of the paper is to identify the volume and structure of foreign direct investment in Poland (in respect to investor's country of origin and target economy area) and to assess Poland's attractiveness to investors contrasted with chosen central and east European countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 357-368